Normal Head Shape Parameters in the First 2 Years of Life and Effect of Helmet Therapy - Wilbrand, Jan-Falco; Kaps, Kerstin; Tabak, Darko; Bierther, Uta; Wilbrand, Martina; Neubauer, Bernd Axel; Pons-Kuehnemann, Joern; Howaldt, Hans-Peter; Hahn, Andreas (Neuropediatrics, 2017)
Objective The treatment of a positional head deformity in infancy is a controversial issue. The aim of this study was to explore the effects of helmet therapy on positional plagiocephaly and brachycephaly.Patients and Methods We determined cranial vault shape parameters in 348 healthy children during the second year of life, combined them with preexisting data from more than 400 subjects younger than 12 months, and related retrospectively the data of 1,531 children obtained before and after treatment with individual molding helmets to these newly generated normative values.Results The number of subjects with cranial vault asymmetry values > 97th percentile decreased by 85.5% from 1,361 before to 197 (p < 0.01) after helmet therapy, while the number of individuals with cranial vault asymmetry index values > 97th percentile declined by 87.7% from 1,353 to 167 (p < 0.01). Similarly, the number of infants with cranial index values > 97th percentile diminished by 66.8% from 885 to 294 (p < 0.01).Conclusions These findings do not finally prove, but they support the idea that helmet treatment is effective and meaningful in preventing permanent head deformities in infants with severe deformation. The normative anthropometric data generated in this study will allow investigating the natural course and effects of various therapies on infant cranial shape objectively.
Keywords: positional plagiocephaly; normative data; helmet therapy; anthropometry